Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-4632.2010.04745.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA‐B*1502 allele with carbamazepine‐induced toxic epidermal necrolysis and Stevens–Johnson syndrome in the multi‐ethnic Malaysian population

Abstract: HLA-B*1502 is strongly associated with CBZ-induced TEN/SJS in the Malay population in Malaysia, as has been seen in Han Chinese in Taiwan. This indicates that the genetic association apparent in the incidence of CBZ-induced TEN/SJS is linked with the presence of HLA-B*1502, irrespective of racial origin. Screening of patients for this genetic marker can help to prevent the occurrence of TEN/SJS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 26 publications
(21 reference statements)
9
154
1
2
Order By: Relevance
“…The tight association of HLA-B*1502 with CBZ-SJS/TEN was further confirmed in our extended study group of now close to one hundred CBZ-SJS/TEN patients, and has also been confirmed in other Southeast Asian populations/countries where the allele is prevalent [9][10][11][12][13]. These patients were from widely separated geographic areas (Taiwan, Hong Kong, China, Australia, Europe and United States); however, all patients identified were Southeast Asians or Asian descendants.…”
Section: Association Of Hla-b*1502 With Cbz-sjs/tensupporting
confidence: 61%
“…The tight association of HLA-B*1502 with CBZ-SJS/TEN was further confirmed in our extended study group of now close to one hundred CBZ-SJS/TEN patients, and has also been confirmed in other Southeast Asian populations/countries where the allele is prevalent [9][10][11][12][13]. These patients were from widely separated geographic areas (Taiwan, Hong Kong, China, Australia, Europe and United States); however, all patients identified were Southeast Asians or Asian descendants.…”
Section: Association Of Hla-b*1502 With Cbz-sjs/tensupporting
confidence: 61%
“…Few studies explored the rate of CADRs seen by a hospital dermatology department; CADRs accounted for 1.38% of all referrals to university hospital department of dermatology in Denmark and 1.5 % of total dermatology consultations seen at a hospital in Tunisia [7,12]. HLA-B 1502 a known genetic marker for both carbamazepine and phenytoin induced CADR was reported to be present in 47 of 300 (15.7%) normal Malay controls, 5.7% of 300 normal chinese controls and in none of the 100 normal Indian controls, in a study of 21 carbamazepine induced TEN/ SJS in Malaysia [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*1502 as a marker for carbamazepine-induced SJS is well established in the Han Chinese by different studies [1,10]. In a study from India, Mehta et al, found that six out of eight patients had HLA-B*1502 while none of the 10 controls were found to be positive.…”
Section: Trigeminal Neuralgia 08mentioning
confidence: 99%
“…Several reports have implicated carbamazepine as among the most common causes for SJS/TEN in Indians too. 18,19 According to the Pharmaco vigilance programme an ADR is said to be serious if it resulted in death, life threatening events, hospitalization or prolongation of hospitalization, disability, congenital-anomaly or required intervention to prevent permanent impairment / damage. Among the 25 CADRs reported after CBZ, 80% were labelled serious and life threatening and required hospitalization and acute intervention.…”
Section: Drug Induced Hypersensitivity Syndrome (Dhs) Is Sometimes Camentioning
confidence: 99%